Integrating Carrot Agro-Industrial Waste Into Sustainable Poultry Feeding Systems - Anugrah, Muhammad Rajab; Semaun, Rahmawati; Rasbawati (Integrated and Sustainable Agriculture, 2024)
Integrating agro-industrial waste into poultry feeding systems is a strategic approach to enhancing sustainability and feed resource efficiency. This study evaluated the potential of carrot agro-industrial waste as an alternative feed ingredient in broiler diets, focusing on its effects on crude protein and crude fiber contents. The experiment employed a completely randomized design with four dietary treatments containing carrot waste flour at 0, 3, 6, and 9%. Diets were formulated to be isoenergetic and isoprotein. Crude protein and crude fiber contents were analyzed using standard AOAC methods and subjected to analysis of variance. The results indicated that carrot waste flour inclusion significantly affected crude protein and crude fiber contents (P < 0.01). Crude protein content increased with carrot waste inclusion up to 6% and declined at the 9% level, while crude fiber content increased with higher inclusion levels. The 6% inclusion level provided the most optimal balance between enhanced crude protein and acceptable crude fiber content. In conclusion, moderate inclusion of carrot agro-industrial waste, particularly at 6%, improves the nutritional quality of broiler diets and supports integrated and sustainable poultry feeding systems within circular agriculture frameworks.